Making and breaking in an art education makerspace - Robert W. Sweeny (Journal of Innovation and Entrepreneurship, 2017)
In this article, the author will outline the process of setting up a makerspace in an art education program on a US university campus. The challenges that were encountered will be discussed, as will the successful elements. In the conclusion, the author will provide the reader with a number of suggestions for integrating a makerspace into art education teacher preparation programs.
Keywords: 650